2021
DOI: 10.3390/molecules26206153
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile, Antioxidant Capacity and Antimicrobial Activity of Nettle Leaves Extracts Obtained by Advanced Extraction Techniques

Abstract: Nettle is a widely known plant whose high biological activity and beneficial medicinal effects are attributed to various bioactive compounds, among which polyphenols play an important role. In order to isolate polyphenols and preserve their properties, advanced extraction techniques have been applied to overcome the drawbacks of conventional ones. Therefore, microwave-assisted extraction (MAE) has been optimized for the isolation of nettle leaves polyphenols and it was compared to pressurized liquid extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 55 publications
5
38
0
Order By: Relevance
“…Acetone (30%) proved to be the most effective solvent for isolation of polyphenols from fennel seeds, followed by water and 30% ethanol. These results are in accordance with a previous study on optimization of MAE of nettle leaves' polyphenols [15]. Sulaiman et al (2011) [36] reported that when compared to aqueous ethanol and aqueous methanol and water, 70% aqueous acetone was the most effective solvent for recovery of polyphenols from vegetables.…”
Section: Mae Optimizationsupporting
confidence: 92%
See 3 more Smart Citations
“…Acetone (30%) proved to be the most effective solvent for isolation of polyphenols from fennel seeds, followed by water and 30% ethanol. These results are in accordance with a previous study on optimization of MAE of nettle leaves' polyphenols [15]. Sulaiman et al (2011) [36] reported that when compared to aqueous ethanol and aqueous methanol and water, 70% aqueous acetone was the most effective solvent for recovery of polyphenols from vegetables.…”
Section: Mae Optimizationsupporting
confidence: 92%
“…Therefore, MAE was carried out varying the extraction solvent, temperature, irradiation time and microwave power to observe the influence of extraction parameters on the recovery of phenolic compounds from fennel seeds. For the solvent effect, 30% aqueous solutions of ethanol and acetone were compared to water, according to previous literature reports confirming the suitability of these binary solvent systems for the isolation of plant polyphenols [15,[28][29][30]. The temperature, time and microwave power span taken into consideration were selected based upon previous research on MAE of polyphenols [14,15,31].…”
Section: Mae Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…MBC of the seaweed extracts was determined as the lowest concentration at which no microbial growth was detected on agar plates after subcultivation of bacterial suspension pipetted from wells where MIC was determined and from wells with higher extract concentrations [53].…”
Section: Determination Of the Antimicrobial Activitymentioning
confidence: 99%